Remote Regio- and Stereocontrol by the Sulfinyl Group: Diels-Alder Reaction of Sulfinyl Dienols and 8,8-Dimethylnaphthalene-1,4,5(8h)-Trione - Caroli-Rezende, M; Almodovar-Fajardo, I (2013)
Sin Editorial Disponible